Competitive Policy And Knowledge Economy Indicators In Developing Countries - laref, khadidja; Meziane, Mohamedtawfik (Finance and Business Economies Review, 2020)
This research paper aims to analyze the reality of the indicators of the knowledge economy and its contribution to forming the competitive advantages of developing countries, because the global economy today is going through a transitional phase from an industrial society to a knowledge society. This is translated by the role of education, research and development (R&D) in the formation of the human individual, and the importance of innovation rather than industrialization in improving business competitiveness. In the current context of globalization, developing countries have increasingly improved industrial policy by relying more on a competitive industrial policy aimed at enhancing investment in human capital and analyzing both the inputs and outputs of the technical process. In this direction, it is worth noting the importance of government actors in enhancing government spending and creating a competitive advantage among business organizations, and on the one hand measuring the performance of Mediterranean developing countries, including Algeria, in their ability to create an effective national innovation syste